Malaria prevention using antibodies: A promising approach to passive protection - Qureshi, Muhammad Qasim; Muhammad Khawer; Muneeb ur Rehman (Journal of the Pakistan Medical Association, 2023)
Madam, malaria is a parasitic infection that is one of the leading causes of death in developing countries like Pakistan. According to WHO, an estimated 241 million malaria cases were reported in 2020 (1). Vaccines have been developed to prevent malaria but with limited efficacy. Using next-generation antibodies can be a possible option to reduce malarial infection. Recently, a phase 1 trial conducted by NIAID at the National Institute of Health (NIH), USA, clinical centre has reported promising results with using intravenous and subcutaneous antibodies for malaria prophylaxis in healthy adults(2). Chemoprophylaxis drugs like chloroquine, mefloquine, and atovaquone/proguanil has been used for malaria in Pakistan, but it has led to the generation of drug-resistant strains(3). WHO approved a subunit vaccine for children in 2021 but it has limited efficacy and risk of severe side effects(4). Considering these aspects, the using monoclonal antibodies may be a practical step toward decreasing the number of malaria cases. The trial demonstrated that using antibodies in adults who had not had malaria or vaccinated previously was associated with substantial passive immunity. The immunity was tested after exposing the participants to controlled human malaria infection. Parasitemia, as determined by PCR, developed in all 6 participants from the control group, while only two out of 17 participants from the intervention group showed parasitemia (2). Pakistan reports malaria cases throughout the year, with most cases occurring in the summer (5). Using malaria antibodies can help advance protection in countries like Pakistan with seasonal transmission. Although, the economic cost of using this intervention must be considered especially for developing countries.